The marketing of an unsought service through an unobtrusive medium: a content analysis of the websites of members of the National Funeral Directors Association of South Africa - Cerneels Coetzee; Tania Maree; Cornelius van Heerden (Communicare)
The marketing of intangible services – particularly of unsought services such as those of the funeral industry – can be said to pose inherently unique challenges to marketers. Because of the unsought nature of funeral services, consumers generally avoid the industry, primarily because the services offered by the funeral industry are associated with death and grief. This article reports on some selected findings of an evaluation of the effectiveness of funeral-home websites of members of the National Funeral Directors Association (NFDA) of South Africa. The focus of this paper is on the user-friendliness of the websites under consideration. A quantitative content analysis of the websites in question was conducted to collect the relevant data. The findings indicate that the majority of the websites may be considered satisfactory in terms of their overall ease of use. As well as some recommendations for improvements to the websites, a few suggestions for future research are also provided.